SEAFLOOR MORPHOLOGY INFLUENCES ON CURRENT CONDITION IN A SUNDA STRAIT BRIDGE PROJECT USING NUMERICAL MODEL - Franto Novico; I Nyoman Astawa; Adi Sinaga; Arif Ali (BULLETIN OF THE MARINE GEOLOGY, 2015)
It has been more than 50 years since the idea to construct the bridge of Sunda Strait was inspirited by Prof. Sedyatmo. This issued is very important due to accelerate the economic growth between Sumatera Island and Java Island which is known as the densest population in the Indonesia. However, until today the bridge is still not construct yet because the high budget and the lack of technical data are still being problems. One of the most important data is current condition along the Sunda Strait. Unfortunately, no one has been clearly studied about current condition along Sunda Strait. Therefore, the information about current condition would be completed to fulfil the lack of data and information. The RV Geomarine I, as a research vessel conducted the survey in October 2012 that one of the objectives is to get the impression about the current condition around the bridge plan. Attaching echo sounder of bathy 1500 to get the depth profile and applied the RD Instrument ADCP Mobile Workhorse Monitor 300 kHz to collect the real current data and analyze the current using numerical model by Mike 21 were carried out to describe the condition of the current around the bridge proposed. In addition, the detail flexible mesh of hydrodynamic model is applied along bridge plan to analyse the current condition that caused by seafloor morphology. Based on the ADCP data it would be seen that the highest velocity record of the current occurs at October 18th 2012 at line 19 with the value 2.63 m/sec. Nevertheless, the numerical model shown the highest current velocity occurs around the northwest of Sangiang Island where the speed attains more than 4.59 m/sec.Keywords: Seafloor morphology, Sunda Strait bridge, current condition, numerical model, the Sunda Strait Ide pembangunan jembatan di Selat Sunda telah ada lebih dari 50 tahun yang lalu, hal tersebut diinspirasikan oleh Prof. Sedyatmo. Isu tersebut sangat penting untuk mengakselerasi pertumbuhan ekonomi di antara Pulau Sumatera dan Pulau Jawa, dimana diketahui sebagai pulau yang memiliki populasi terpadat di Indonesia. Namun, hingga saat ini jembatan tersebut masih belum terbangun disebabkan oleh masalah keuangan, dan kurangnya data teknis penunjang. Salah satu data terpenting adalah data arus di Selat Sunda. Namun, tidak ada satupun yang secara khusus melakukan penyelidikan tentang arus di sepanjang Selat Sunda. Untuk itu, informasi tentang kondisi arus akan dilakukan untuk memenuhi kekurangan data dan informasi. KR Geomarin I, sebagai kapal riset telah melakukan penelitian pada bulan oktober 2012 dimana salah satu tujuannya adalah untuk mengetahui kondisi arus di sekitar rencana jembatan. Dengan menggunakan echousounder bathy 1500 untuk mendapatkan profil kedalaman dan RD Instrument ADCP Mobile Workhorse Monitor 300 khz untuk mengumpulkan data arus sesaat dan melakukan analisa arus di sekitar rencana jembatan menggunakan model numeric Mike 21. Detail flexible mesh di sepanjang rencana jembatan diaplikasikan pada model hidrodinamika untuk menganalisa kondisi arus di sekitar area tersebut. Berdasarkan hasil survey ADCP maka dapat diketahui nilai kecepatan air terbesar terhadi pada tanggal 18 Oktober 2012 pada lintasan 19 dengan nilai 2,63 m/det. Sementara, hasil model numeric menunjukkan nilai arus tertinggi terjadi di sekitar barat laut Pulau Sangiang dengan kecepatan lebih dari 4.59 m/det. Kata kunci: Morfologi dasar laut, jembatan Selat Sunda, kondisi arus, model numeric, Selat Sunda